ANALISIS KINERJA PERBANKAN PADA PT BANK KOOKMIN BANK (KB) BUKOPIN Tbk., PERIODE 2019-2021 - Elsa Maulidia (2022)
The bank's financial performance is a description of the bank's achievements in its operations, both regarding financial aspects, collection and distribution of funds, marketing, human resources and technology which are part of the bank's overall performance. This final project aims to describe the financial performance of banks based on the results of banking financial ratio analysis. The results of the banking financial ratio analysis on the liquidity ratio analysis show the condition of the financial performance of PT. Kookmin Bank (KB) Bukopin Tbk., the period 2019-2021 can be said to be less good. The average LDR of 108.92% does not meet the standards set by POJK. The results of the solvency ratio analysis, the condition of the financial performance of PT Bukopin (Persero) Tbk in 2019-2021 can be said to be good because the average CAR is 14.98%, this value has complied with the provisions of the POJK. In the profitability ratio analysis, the condition of financial performance can be said to be not good, because the average ROA is below 0%, which is -2.77%, this value is below the POJK provisions. In the analysis of the ratio of earning assets, the condition of financial performance can be said to be unfavorable, because the average NPL is 9.08%, not meeting the standards set by POJK. From all financial ratio analysis, it can be seen how the financial condition of PT. Bukopin (Persero), Tbk.